A new long-run economic model basis for projecting the finances of the US government - John Mantus; Gaobo Pang; Mark J. Warshawsky (American Enterprise Institute (AEI), 2025)
In the official models for projections and policy analysis used by the Treasury and the Social Security and Medicare Trustees, many key variables are assumed as a continuation of past trends. Even the Congressional Budget Office (CBO), with more sophisticated models, makes certain simplifying assumptions. By contrast, in our model, these variables are simultaneously determined by supply and demand, based on logical functional forms and parameter estimates from the literature or empirical analysis. This approach better reflects real economic relationships-between health care spending, the federal budget, and investment in capital-and changing underlying conditions, especially demographics. Within the next twenty or so years, we find the federal government debt will grow significantly beyond historical experience and should be regarded as unsustainable. We project that debt-to-GDP will be 126 percent in 2033, 179 percent in 2043, and 256 percent in 2053, compared to CBO's 115 percent in 2033 and 166 percent in 2053. Real interest rates rise in the long run, ratcheting interest payments, deficits, and debt in a vicious cycle. Our projection of national health expenditures relative to GDP in 2073 is 30.2 percent, compared to 28.5 percent by the Centers for Medicare and Medicaid Services (CMS) in its alternative projection. These higher costs of health care arise from labor shortage effects in an aging economy because health care is produced in a low productivity, labordependent sector. Health care expenditure increases further deteriorates the federal budget and lowers consumer welfare. We propose that our model serve as the basis for the Trustees Reports and the Financial Report of the U.S. Government.
Keywords: 330; Congressional Budget Office (CBO); Federal budget; federal debt; Fiscal policy; Medicare; Social Security